2018
DOI: 10.3389/fpsyg.2018.00960
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Ethical Climate(s) on Employees’ Behavior: A Social Identity Approach

Abstract: The spread and publicity given to questionable practices in the corporate world during the last two decades have fostered an increasing interest about the importance of ethical work for organizations, practitioners, scholars and, last but not least, the wider public. Relying on the Social Identity Approach, we suggest that the effects of different ethical climates on employee behaviors are driven by affective identification with the organization and, in parallel, by cognitive moral (dis)engagement. We compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 72 publications
(94 reference statements)
4
92
0
3
Order By: Relevance
“…Past research has examined employees' behavior predicted by several factors, such as the creation of a positive organizational climate to stimulate safe work behavior in employees (Smith-Crowe et al, 2003). Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018). Ethical climates such as friendship utilizing the social identity approach projected better behaviors and attitudes of employees concerning many outcomes including turnover intention (Teresi et al, 2019).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Past research has examined employees' behavior predicted by several factors, such as the creation of a positive organizational climate to stimulate safe work behavior in employees (Smith-Crowe et al, 2003). Employees' behavior, including OCB, was positively affected by the ethical climate through the social identity approach (Pagliaro et al, 2018). Ethical climates such as friendship utilizing the social identity approach projected better behaviors and attitudes of employees concerning many outcomes including turnover intention (Teresi et al, 2019).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…In recent years, researchers as well as practitioners have focused their attention on this construct, considering its direct influence both on individual and organizational outcomes and behaviors (for a recent review, see Newman et al, 2017). In particular, when comparing ethical climates that promote prosocial behavior with those suggesting more individualistic behavior, it emerges that the former are more strongly associated with work performance and employees’ positive attitudes and behaviors (e.g., Peterson, 2002; Briggs et al, 2012; Ehrhart and Raver, 2014; Mayer, 2014; Pagliaro et al, 2018). Thus, it seems crucial for organizations to understand the positive and negative consequences of different kinds of ethical climates in order (a) to avoid the associated financial and sociopsychological costs and (b) to rely on those climates that, on the contrary, may increase employees’ positive relationship with the organization and positive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Other empirical studies have shown that the ethical climate indirectly influences OCBs through other mediation and moderation variables. This is the case, for example, of Pagliaro et al (2018) who evaluated the impact of two types of ethical climate namely: ethical organizational climate of self-interest, and an ethical organizational climate of friendship on Organizational Citizenship Behaviors (OCBs), and Counterproductive Work Behaviors (CWBs). The results of their research indicate that the two ethical climates were independently related to organizational identification and moral disengagement.…”
Section: -Conceptuel Framework 3-1 Ethical Climate and Organizationmentioning
confidence: 99%
“…Firstly, our study brings to human resources managers new knowledge to optimize and improve the employees OCB through the implementation of ethical climate within the company. Ethics has positive effects on behavior and attitudes of employees (Pagliaro et al ,2018) and improve their employees contextual performance including OCBs (Coleman et Borman ,2000, Motowidlo et al 2000. Secondly, research on OCB have granted limited importance to developing mechanisms for these behaviors especially in organizations that wish to use OCB to provide better quality of service (Wolfe Morrison, 1996).…”
Section: -Conclusion and Managerial Implicationsmentioning
confidence: 99%